Child Marriage in Health Psychology: A Narrative Literature Review - Pujhana, I Kadek Wahyu (Faculty of Psychology Universitas Gadjah Mada, 2025)
Child marriage is a public health concern that significantly affects the physical, mental, and social well-being of adolescent girls. While prevention strategies often target structural factors, such as poverty and education, they tend to overlook the psychological influences underlying early marriage decisions. This study explored child marriage from a health psychology perspective, using the theory of planned behavior (TPB) as the primary analytical framework. A narrative literature review was conducted by analyzing 26 peer-reviewed articles published from 2016 to 2025. The findings revealed that permissive attitudes toward early marriage, strong social pressure, and low perceived behavioral control are key contributors to the persistence of the child marriage phenomenon. The consequences include adolescent pregnancy, childbirth complications, gender-based violence, and mental health issues, such as depression and anxiety. These insights underscore the importance of TPB-based interventions aimed at reshaping attitudes, challenging social norms, and empowering girls with behavioral control. This review offers a foundation for developing more effective and context-sensitive strategies to prevent child marriage through a health psychology approach.